Psychological profiles of risk for antenatal depression and anxiety in Iranian sociocultural context - Zahra Alipour; Gholam Reza Kheirabadi; Ahmad Ali Eslami; Ashraf Kazemi (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND AND AIM: Mental health issues including depression and anxiety are common in pregnancy worldwide. This study aimed to identify factors associated with mental disorders in a sample of Iranian pregnant women. MATERIALS AND METHODS: A cross-sectional study was conducted among pregnant women referred to a prenatal-care clinic in an urban area, Isfahan, Iran. The questionnaires in this study included the General Health Questionnaire and additional structured questionnaires exploring sociodemographic, obstetric, and economic risk factors and empowerment for decision-making regarding pregnancy, parenting, financial authority, trust, and confidence in health-care staff. Regression analysis was performed to assess the impact of the number of variables on the likelihood of the presence of mental health problems. RESULTS: Overall, 54.2% and 11.7% of the women had anxiety and depression, respectively. No statistically significant associations were reported between anxiety and depression and obstetric characteristics such as gestational age, parity, abortion, previous infertility, unwanted pregnancy, and the screening test results. According to the logistic regression analysis, the predictors of depression and anxiety were acknowledging psychological changes in pregnancy and empowerment for decision-making regarding pregnancy and parenting and financial authority (P < 0.05). CONCLUSIONS: probably, women's empowerment on becoming aware of psychological changes during pregnancy and making decisions on pregnancy, parenting, and financial authority is the factor affecting the mental health of pregnant women.